Retraction Notice - -, - (Jurnal Penelitian dan Pembelajaran IPA, 2018)
Retraction notice to ” The Use of Science Environment Technology and Society (SETS) Learning Model for Enhancing the Critical Thinking Skills and Scientific Attitudes” [Jurnal Penelitian dan Pembelajaran IPA, vol.3, no.1, 2017, pp. 65–73]MaimunahDepartment of Informatica Engineering, Faculty of Technique, Mathematics, and Natural Science Universitas Indraprasta PGRI This article has been retracted. The author have plagiarized part of a paper that had already appeared Formatif: Jurnal Ilmiah Pendidikan IPA Vol.2, No.2, Year 2016 in Indonesian Language and available online at http://journal.lppmunindra.ac.id/index.php/Formatif/article/view/947. One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.